Processing Household Organic Waste into Eco-Enzyme as an Effort to Realize Zero Waste - I Nengah Muliarta; I Ketut Darmawan (Agriwar Journal, 2021)
Households have become one of the sources of waste and their utilization so far is also fairly minimal. Household waste tends to end up in landfills when it can be processed into materials of economic value. Waste ingredients such as vegetable waste or fruit peels can be processed into a multipurpose eco-enzyme liquid. Making eco-enzyme is very simple and can be done by anyone. Eco-enzyme is an organic compound in the form of a complex solution resulting from the fermentation process of kitchen waste materials in the form of fruit peels and vegetable waste. The term Eco-enzyme was initiated by Dr. Rosukon Poompanvong, a founder of the Organic Agriculture Association, Thailand who has researched since the 1980s. A Naturopathy researcher from Penang, Malaysia, Dr. Joean Oon later introduced the term more broadly. The use of eco-enzyme in its development is expanding, so it is not uncommon to be referred to as a multipurpose liquid. This liquid in the environmental field has been commonly used in liquid waste treatment, lake water purification, improved air, and soil quality. Utilization in the field of health is usually used to prevent hair loss, hives, and hand sanitizer. Eco-enzyme is also commonly used as fertilizer and biopesticide. The creation of eco-enzyme not only helps reduce waste disposal to landfills but also becomes an alternative to reducing the use of synthetic chemicals that are harmful to human health and the environment. Awareness of household waste processing into eco-enzyme is also a step in the effort to realize zero waste at the household level.